206k views
4 votes
If f(x) = 2x-1 and g(x) =3x + 5, what is the f(g(5)

2 Answers

3 votes

Answer:

f ( 2 x + 1 ) = 6 x − 2

Explanation:

Set up the composite result function.

f ( g ( x ) )

Evaluate f ( g ( x ) )

by substituting in the value of g into f

. f ( 2 x + 1 ) = 3 ( 2 x + 1 ) − 5

Simplify each term.

Apply the distributive property.

f ( 2 x + 1 ) = 3 ( 2 x )+ 3 ⋅ 1 − 5

Multiply 2 by 3 .

f ( 2 x + 1 ) = 6 x + 3 ⋅ 1 − 5

Multiply 3 by 1 .

f ( 2 x + 1 ) = 6 x + 3 − 5

Subtract 5 from 3 . f ( 2 x +1 ) = 6 x− 2

User Profpatsch
by
5.6k points
7 votes

Answer:

39

Explanation:

g(5) = 3(5) + 5 = 20

f(20) = 2(20) - 1 = 39

User Purefusion
by
4.5k points